El Excentrico, 1963-02-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
February 20, 1963 [20 de febrero de 1963]. Ano 13, No 8. Cover has a photograph of Carole Mann in formal wear and smiling for an advertisment for the United Food Drive. The headline reads, "Talented songstess Carole Mann to appear in Talent Show."